2020
DOI: 10.4314/jasem.v24i4.19
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in Bushmeat from New-Bussa and its environs, Nigeria

Abstract: Bushmeat have provided complimentary protein for human population across the world over the centuries. This study assessed the concentration of heavy metals in bushmeats in New Bussa and its environs. Three carcass of bush meat (Kobus kob (Kob), Tragelaphus scriptus (Bushbuck) and Sylvicapra grimmia (Duiker)) were sourced from the study area. The carcass was digested and concentrations of nine heavy metals (Mn, Fe, Cu, Zn, Pb, Cr, Ni, Co and Cd) were determined using Atomic Absorption Spectrophotometer (AAS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…18 In contrast however, Friant et al 2015 has reported some measure of health risk awareness among hunters engaged in bushmeat processing activities. Other studies indicate that asides the risk of contracting parasitic diseases, bushmeat is also known to contain heavy metals in measures that are sometimes above recommended WHO limits (Ogungbile et al, 2022) 32 that may lead to nervous system illnesses This issue alludes to the dearth of such needed knowledge among the urban populace which may help deter the increasing demand. Without this, consumption may continue unabated and Public health becomes more at risk, with many in danger of contracting zoonotic diseases.…”
Section: Perception On Health Risk and Legal Deterrents Surrounding B...mentioning
confidence: 99%
“…18 In contrast however, Friant et al 2015 has reported some measure of health risk awareness among hunters engaged in bushmeat processing activities. Other studies indicate that asides the risk of contracting parasitic diseases, bushmeat is also known to contain heavy metals in measures that are sometimes above recommended WHO limits (Ogungbile et al, 2022) 32 that may lead to nervous system illnesses This issue alludes to the dearth of such needed knowledge among the urban populace which may help deter the increasing demand. Without this, consumption may continue unabated and Public health becomes more at risk, with many in danger of contracting zoonotic diseases.…”
Section: Perception On Health Risk and Legal Deterrents Surrounding B...mentioning
confidence: 99%
“…Pb level in bushbuck (213.00 ± 3.00 mg kg -1 ) was outrageously the highest. Thus creating a health concern for bush meat consumers in the study area [24].…”
Section: Introductionmentioning
confidence: 99%